The Implementation of Curriculum Policies in State Islamic Madrasahs - Ismail Ismail; Sugeng Sukoco; Syafaruddin Syafaruddin; Makmur Syukri (Universitas Pahlawan Tuanku Tambusai, 2022)
Madrasah internal policies are needed in implementing the curriculum as an effort to adapt to changes and community needs. This study aims to describe the implementation of curriculum implementation policies in state madrasah ibtidaiyah in Central Tapanuli Regency (MIN 3, 4, and 7). This study seeks to describe or describe data obtained from the field or literature related to PAI curriculum management in MIN 3, 4 and 7 Central Tapanuli Regency. The informants or resource persons are the head of the madrasa, the deputy head of the madrasa in the curriculum field, and the teacher of PAI subjects. The results of this study indicate that the overall implementation of the Islamic religious education curriculum in MIN Central Tapanuli Regency is well implemented. It is characterized by (1) planning aspects; includes analysis of the needs and conditions of local communities, analysis of the availability and readiness of resources in madrasas, analysis of supporting programs implemented in the agenda of the annual work meeting (2) implementation aspects; including optimizing the role of supervisors and monitoring the head of madrasah, implementing training to improve the competence and quality of teachers, as well as coordinating with teachers in madrasas in the weekly meeting agenda, (3) evaluation aspects; includes an assessment every year, in the form of program evaluations in the curriculum, planning learning tools, and evaluating students.